2019
DOI: 10.1136/bmjopen-2018-023316
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cardiac surgery operations in hospital episode statistics administrative database, with an OPCS-based classification of procedures, validated against clinical data

Abstract: ObjectivesAdministrative databases with dedicated coding systems in healthcare systems where providers are funded based on services recorded have been shown to be useful for clinical research, although their reliability is still questioned. We devised a custom classification of procedures and algorithms based on OPCS, enabling us to identify open heart surgeries from the English administrative database, Hospital Episode Statistics, with the objective of comparing the incidence of cardiac procedures in administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…those reduced and discharged home directly from the Emergency Department) might not have been captured by our study. Previous work in other surgical settings has found that OPCS4 codes in HES can reliably be used to identify some operations, although this can vary substantially between procedures [39]. However, a range of codes were used to define “revision surgery” and this selection might have influenced the findings.…”
Section: Discussionmentioning
confidence: 99%
“…those reduced and discharged home directly from the Emergency Department) might not have been captured by our study. Previous work in other surgical settings has found that OPCS4 codes in HES can reliably be used to identify some operations, although this can vary substantially between procedures [39]. However, a range of codes were used to define “revision surgery” and this selection might have influenced the findings.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital Episode Statistics (HES) Admitted Patient Care database was interrogated to identify admitted care episodes for adult patients with diagnostic codes relating to high-risk emergency general surgical (EGS) conditions (defined by an associated crude mortality rate greater than 5 per cent 4 , 5 including gastrointestinal ulcer; hernia, bowel ischaemia, bowel obstruction, diverticulitis, peritonitis, liver and biliary conditions, and miscellaneous; Table S1 and Appendix S1 ), and major elective surgery across several surgical subspecialties (colectomy, any rectal resection (proctectomy) 6 , cystectomy (bladder) 7 , oesophagectomy, gastrectomy, pancreatectomy, coronary artery bypass graft) 8 , open abdominal aortic aneurysm (AAA) repair 9 , endovascular aortic aneurysm repair (EVAR) 9 , and carotid endarterectomy 10 ; Table S2 and Appendix S1 ) 11 , 12 .…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with findings from other centres. 20 Further, where OPCS codes are correct, they often do not provide enough granular detail about the operation type for use in research.…”
Section: Discussionmentioning
confidence: 99%